Competitiveness of MSMEs in the Digital Era Through Google Maps Social Media Marketing and Entrepreneurship - Humairoh, Humairoh; Soemadi, Rd Roro Anggraini; Nur, Bimantoro (Dinasti Publisher, 2025)
This study aims to determine the effect of Google Maps social media marketing and entrepreneurship on the competitiveness of Micro, Small, and Medium Enterprises (MSMEs) in the Ciledug area in the digital era. The approach used in this study is quantitative, with the research population being Micro, Small, and Medium Enterprises (MSMEs) in Ciledug, limited to the age range of 20 to 45 years. The sampling technique used a non-probability sampling method with a purposive sampling approach, so that a sample of 100 respondents was obtained. The data analysis tool used was SPSS version 26. The results of the study showed that partially, the Google Maps social media marketing variable had a positive and significant effect on competitiveness, and the entrepreneurship variable had a positive and significant effect on competitiveness. However, simultaneously, both variables, namely Google Maps social media marketing and entrepreneurship, had a positive and significant effect on the competitiveness of MSMEs. The coefficient of determination (R²) value of 0.527 or 53% indicates that the Google Maps social media marketing and entrepreneurship variables are able to explain the variation in competitiveness by 53%, while the remaining 47% is influenced by other variables not studied. This research is expected to contribute as a reference for strategies to increase the competitiveness of MSMEs, especially through the use of social media and improving entrepreneurial skills through relevant business innovation training.